2022
DOI: 10.1021/acs.iecr.1c02514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Cocatalysts and Operating Conditions on the Product Distribution and the Productivity of the CO2 Photoreduction

Abstract: The CO 2 photoreduction is a promising way to convert one of the most abundant greenhouse gases to valuable chemicals. The photoreduction in the liquid phase is limited by the low solubility of CO 2 in water, but this point is overcome here by using an innovative photoreactor, which allows one to work up to pressures of 20 bar, improving the overall productivity. The photoreduction was performed in the presence of Na 2 SO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…3.6.1. Photo-Reduction of CO 2 Figure 6 illustrates some of the most promising photo-catalysts employed for the conversion and valorization of carbon dioxide, which have also been reported elsewhere [41,71,72]. The most active material, at least in terms of formic acid productivity, is the bi-metallic photo-catalyst 1 wt% (Au 2 Ag 8 ), leading to 9.5 mol/kg cat h (±5%) and outperforming the non-promoted titania P25 (3.2 mol/kg cat h (±5%)).…”
Section: Photo-catalytic Testsmentioning
confidence: 86%
“…3.6.1. Photo-Reduction of CO 2 Figure 6 illustrates some of the most promising photo-catalysts employed for the conversion and valorization of carbon dioxide, which have also been reported elsewhere [41,71,72]. The most active material, at least in terms of formic acid productivity, is the bi-metallic photo-catalyst 1 wt% (Au 2 Ag 8 ), leading to 9.5 mol/kg cat h (±5%) and outperforming the non-promoted titania P25 (3.2 mol/kg cat h (±5%)).…”
Section: Photo-catalytic Testsmentioning
confidence: 86%
“…The selectivity can be tuned by changing photocatalyst formulation, e.g., adding a co-catalyst (for instance, Cu 2+ favours the production of methanol, while Au is often reported to favour selectivity to CH4); changing temperature, pressure or pH; creating oxygen vacancies; or doping with non-metals. By optimising these factors, it is possible to tune the selectivity to favour the production of specific desired products [38]. An efficient way to compare the performances of the photocatalysts can be achieved by calculating the total stored energy [39,40].…”
Section: Fundamentals Of Heterogeneous Photocatalysis and Mechanismmentioning
confidence: 99%
“…The addition of NaOH increases the solubility of CO2 with respect to pure H2O because OH − ions react with the CO2 to produce CO3 2− and HCO3 − . It has been proposed that a high concentration of HCO3 − in the system can accelerate the photoreduction reaction, improving its performance [38,72]. 3.…”
Section: Slurry Photoreactorsmentioning
confidence: 99%
“…To overcome these limitations, metal nanoparticles (NPs) are often loaded on the surface of the semiconductor photocatalyst as cocatalysts. Previous studies have reported that metal NPs or metal oxide NPs consisting of platinum, [26] palladium,[ 26l , 26u , 26ab , 26af , 27 ] gold,[ 26l , 26aa , 26ab , 26ac , 26ai , 26aj , 27k , 28 ] rhodium,[ 26z , 26al , 29 ] silver,[ 26l , 26ac , 26ai , 26aj , 26am , 27k , 30 ] ruthenium,[ 26aj , 26ak , 28b , 31 ] copper, –[ 26aj , 27g , 27k , 32 ] nickel,[ 27h , 32n , 33 ] molybdenum, [34] titanium,[ 32x , 35 ] indium, [36] or iridium, [37] can function as CRR cocatalysts. In particular, Pt and PdNPs are used for the hydrogenation reactions because they are favorable for the adsorption and desorption of protons and thereby easy to produce CH 4 .…”
Section: Cocatalyst Used For Photocatalytic Crrmentioning
confidence: 99%